Enhancement of head yield and quality of cabbage (Brassica oleracea) by combining different sources of nutrients - CHATTERJEE, RANJIT; JANA, J C; PAUL, P K (The Indian Journal of Agricultural Sciences, 2012)
The present study was aimed to study on influence of different nutrient sources on important quality attributes of cabbage cv. Golden Acre. The field experiment was conducted during 2005–06 and 2006–07 with 14 different treatments by combining inorganic and different organic sources of plant nutrients. The marketable cabbage heads from different treatments were studied for yield and different quality attributes. The pooled result revealed that cabbage head yield and its shelf life, TSS, vitamin A and vitamin C contents were significantly influenced by the application of different sources of nutrients. Vermicompost emerged as better organic nutrient source over farmyard manure. Inoculation with Azophos, a commercial biofertilizer preparation containing the Azotobacter and phosphate-solubilizing bacteria exerted more positive result over uninoculated treatments and benefits of biofertilizer application were more in presence of vermicompost as compared to farmyard manure. The maximum head yield (27.86 tonnes/ha), shelf-life (12 days), head firmness (93.32 kg/ cm2) as well as TSS (4.18º Brix), vitamin A (126.76 µg/100g), vitamin C (44.62 mg/100g) and lowest nitrate content of head (217.17 mg/kg) were realized for the plants grown with the application of 75% of recommended inorganic fertilizers along with vermicompost (5 tonnes/ha) in presence of biofertilizers. Substitution of 25% recommended inorganic nitrogen with higher levels of organic manure and biofertilizer prolonged shelf-life as well as improved nutritional qualities of cabbage heads.